The air in the house with rubber flooring - Fediaj, B. (Енергетика і автоматика, 2015)
The air in the premises for keeping cattle determined by heat-humidity conditions, the balance of hazards in the volume space. Modern rubber flooring, as opposed to organic, do not provide absorption NH3. The article deals with the issue of changing air regime building on keeping cattle according to a constructive solution roofing layer floor.